2020
DOI: 10.1002/celc.202000989
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes@Nickel Cobalt Sulfide Nanosheets for High‐Performance Supercapacitors

Abstract: As new and alternative energy storage devices to batteries and traditional capacitors, supercapacitors exhibit both high power and high energy density as well as good cycle life. NiCo2S4, a spinel‐structured transition metal sulfide with a high specific capacity, is considered to be a promising electrode material for supercapacitors with great application potential. However, the poor electrical conductivity of NiCo2S4 results in poor rate and cycle performance of the material, which limits its practical applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Because of the insertion of metal cations and H 2 O molecules, the distance between V 2 O 5 layers has been increased, which is more conducive to the intercalation and deintercalation of Zn 2+ . After this, a variety of cations were found to have similar effects, such as monovalent ions Li + [16], Na + [17], K + [18], NH 4 + [19][20][21], divalent ions Ca 2+ [22] and Mg 2+ [23], and transition metal ions Ni 2+ [24] and Co 2+ [25,26]. The electrochemical properties from previous studies have been compared and shown in Table S1.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the insertion of metal cations and H 2 O molecules, the distance between V 2 O 5 layers has been increased, which is more conducive to the intercalation and deintercalation of Zn 2+ . After this, a variety of cations were found to have similar effects, such as monovalent ions Li + [16], Na + [17], K + [18], NH 4 + [19][20][21], divalent ions Ca 2+ [22] and Mg 2+ [23], and transition metal ions Ni 2+ [24] and Co 2+ [25,26]. The electrochemical properties from previous studies have been compared and shown in Table S1.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Researches indicate that, compared single-component suldes, binary metal suldes have higher specic capacity owing to their more redox reactions. 24,25 Nickel-cobalt sulde possess the fast Faraday reaction from the synergistic reaction of nickel and cobalt and it is reckoned as a promising candidate with enhanced electrocapacitive property toward energy-storage devices. [26][27][28][29] To date, nickel-cobalt suldes with various nanostructures, including nanowires, nanosheets and nanoparticles, have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…This could be ascribed to the limited exposure of the active sites within the structure of the active component that otherwise would be fully utilized. Thus, the increased exposure of more active areas of transition metal compounds has been addressed by various strategies such as changing the morphology, enhancing the dispersion such as by loading NiCo 2 S 4 on the surface of carbon nanotubes [13], creating pores, and so on [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%